Impact of volume indices in bioelectrical impedance measurement on the assessment of cardiac function indices by echocardiography in hemodialysis patients - Yudan Wang; Yang Wang; Shun Wu; Na Xu; Zhaoyong Zhang; Zhenmin Ruan; Rui Wang; Xin Geng; Chuanzhen Zhang; Zhiyong Luan; Guofang Chen; Hongqi Ren (Renal Failure)
Introduction Cardiovascular events resulting from volume overload are a primary cause of mortality in hemodialysis patients. Bioelectrical impedance analysis (BIA) is significantly valuable for assessing the volume status of hemodialysis (HD) patients. In this article, we explore the correlation between the volume index measured by BIA and the cardiac function index assessed by echocardiography (ECG) in HD patients.Methods Between April and November 2018, we conducted a cross-sectional study involving randomly selected 126 maintenance HD patients. Comprehensive data on medical history and laboratory test results were collected. Subsequently, we investigated the correlation between volume indices measured by BIA and cardiac function parameters by ECG.Results We discovered a significant correlation between the volume indices measured by BIA and various parameter of cardiac function. The Left Ventricular Hypertrophy (LVH) group exhibited higher levels of the percentage of Extracellular Water (ECW%) and the percentage of Total Body Water (TBW%) compared to the Non-LVH group. Extracellular Water (ECW) and Third Interstitial Fluid Volume (TSFV) were identified as independent risk factors for Left Ventricular Mass (LVM), and both demonstrated a high predictive value for LVM. ECW% emerged as an independent risk factor for the Left Ventricular Mass Index (LVMI), with a high predictive value for LVMI.Conclusion ECW and TSFV were found to be positively associated with cardiac function parameters in HD patients.